2018
DOI: 10.1007/s12028-018-0539-3
|View full text |Cite
|
Sign up to set email alerts
|

Semi-quantitative Cough Strength Score as a Predictor for Extubation Outcome in Traumatic Brain Injury: A Prospective Observational Study

Abstract: SCSS has shown promise in predicting successful extubation in TBI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…S4 in the additional material). High risk of bias was related to the study participation in eight studies [ 47 , 57 , 78 82 , 85 ], to study attrition in one study [ 33 ], to prognostic factor measurement in one study [ 7 ], to the outcome measurement in two studies [ 29 , 77 ] and to study confounding in five studies [ 27 , 65 , 78 , 81 , 85 ]. The remaining studies had low or unclear risk of bias for each of the six domains.…”
Section: Resultsmentioning
confidence: 99%
“…S4 in the additional material). High risk of bias was related to the study participation in eight studies [ 47 , 57 , 78 82 , 85 ], to study attrition in one study [ 33 ], to prognostic factor measurement in one study [ 7 ], to the outcome measurement in two studies [ 29 , 77 ] and to study confounding in five studies [ 27 , 65 , 78 , 81 , 85 ]. The remaining studies had low or unclear risk of bias for each of the six domains.…”
Section: Resultsmentioning
confidence: 99%
“…The predictive value of a successful SBT for ventilator liberation in patients with brain injury is largely unknown. Recent studies have demonstrated higher extubation failure rates after a successful SBT in patients with brain injury compared with general critically ill patients (19)(20)(21)(22)(23). After a successful SBT, extubation failure rates between 31% and 46% have been reported in patients with brain injury.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, 10-14% of general critically ill patients completing an SBT failed ventilator liberation (24)(25)(26)(27). Reasons for the high failure rates in patients with brain injury may be related to upper airway function or neurological status (19,21,23). Therefore, guidelines specifically recommend assessment for airway protective ability, including suctioning frequency, cough strength, and mental status (11,28).…”
Section: Introductionmentioning
confidence: 99%
“…This classi cation is divided into three grades: strong, medium, and weak. There have also been four [8,9,12,17] studies which looked for any correlation between a patient's cough ability and the effectiveness of noninvasive mechanical ventilation [10] . These studies demonstrated that the worse the cough ability, the higher their risk of failing noninvasive mechanical ventilation, and the higher their in-hospital mortality [15][16] .…”
Section: Introductionmentioning
confidence: 99%
“…However, these studies mainly focused on the cough ability of patients receiving mechanical ventilation, there is still a lack of data comparing patients' initial cough ability and outcomes. This will be a prospective, observational study using the Cough Re ex Intensity Score, which is based on a previously proposed cough strength classi cation [17,21,23] . This study will aim to determine whether the Cough Re ex Intensity Score is effective at assessing a patient's risk for airway sputum obstruction, respiratory infection, or mechanical ventilation.…”
Section: Introductionmentioning
confidence: 99%